The Influence of Financial Performance and Non-Financial Performance on Market Value of Banking Companies Listed on the Indonesia Stock Exchange 2020–2024 - Muhammad Wildan Farhan Wildan; Desmy Riani; Hurriyaturrohman (Jurnal Mahasiswa Akuntansi dan Bisnis (JMAB), 2026)
This study aims to analyze the influence of financial performance and non-financial performance on the market value of companies in the banking sector listed on the Indonesia Stock Exchange for the 2020–2024 period. Financial performance is proxied by Return on Assets (ROA), non-financial performance is proxied by the Environmental, Social, and Governance (ESG) Score, while market value is measured using Price to Book Value (PBV). This study uses a quantitative method with secondary data obtained from company annual reports, the Indonesia Stock Exchange, and Bloomberg ESG Data Service. The sampling technique used purposive sampling, resulting in 13 banking companies with 65 observations. Data analysis was performed using panel data regression (Random Effect Model) with the EViews 12 application. The results show that financial performance (ROA) has a positive and significant effect on market value (PBV), while non-financial performance (ESG Score) has no significant effect on market value. Furthermore, financial performance and non-financial performance simultaneously have no significant effect on market value.